Cryo‐scanning electron microscopy investigation of the Octopus Vulgaris arm structures for the design of an octopus‐like arm artefact. Issue 12 (30th October 2015) - Minnocci, Antonio; Cianchetti, Matteo; Mazzolai, Barbara; Sebastiani, Luca; Laschi, Cecilia
ABSTRACT: Octopus vulgaris is a cephalopod of the Octopodidae family. It has four pairs of arms and two rows of suckers which perform many functions, including bending and elongation. For this reason the octopus was chosen as model to develop a new generation of soft‐body robots. In order to explain some of the fine structures of the octopus arm in relation to its specific ability, we examined the external and internal structures of O. vulgaris arms in a frozen‐hydrated state using cryo‐scanning electron microscopy. The arms showed skin with a very complex design that is useful to elongation, and a pore pattern distribution on their surface which is functional to cutaneous oxygen uptake. The analysis of freeze‐fractured frozen‐hydrated arm samples allowed us to describe the developmental differences in the relative proportion of the areas of axial nerve cord, intrinsic and extrinsic musculature, in relation to the growth of the arms and of the increase in functional capability. In the suckers, we analyzed the shedding mechanisms in the outer part of the infundibulum and described the outer and inner characteristics of the denticles, showing in detail their pore system, which is fundamental for their ability to explore the environment. These results are discussed by considering their possible application in the design of new octopus‐like artefacts, which will be able to take advantage of some of these ultrastructure characteristics and achieve advanced bioinspired functionalities. Microsc. Res. Tech. 78:1133–1145, 2015 . © 2015 Wiley Periodicals, Inc.